KUALITAS BATUAN BEKU ANDESITIS BERDASARKAN PENDEKATAN KUAT TEKAN DAN PETROLOGI - -, Irvan Sophian; -, Aton Patonah; -, Febriwan Mohamad (Bulletin of Scientific Contribution, 2011)
The quality of infrastructure is related to the materials to be used, especially rock strength. Infrastructure usually uses the rock material as foundation, road materials, etc. Rock samples were taken from Lagadar-Cimahi and Licin-Cimalaka. Petrographic analyses and point load tests were carried out to determine physical and mechanical characteristics. Rock types of Lagadar are andesite and basaltic and Cimalaka are andesite, basalt, and diorite. Rocks of Lagadar are stronger than Licin based on point load test. Point load test of Lagadar rock samples for andesite ranges from 8.17 - 30.57 kg/cm2, basalt ranges from 47.68 -144.03 kg/cm2, and point load test of andesite, basalt, and diorite from Cimalaka ranges between 4.08 - 10.34 kg/cm2, 4.09 -13.83 kg/cm2, and 6.12 kg/cm2 respectively. Rock strength is influenced by mafic mineral content, void ratio, porosity, texture, rock structures, and the degree of weathering.